Future perspective on redox flow batteries : Aqueous versus nonaqueous electrolytes - Tang, Lina; Leung, Puiki; Xu, Qian; Mohd Rusllim, Mohamed; Dai, Shuyang; Zhu, Xun; Flox, Cristina; Shah, Akeel A. (Elsevier Ltd, 2022)
The unique architecture of redox flow batteries enables energy and power to be decoupled and scaled up more easily than conventional batteries. With the objectives of achieving the cost target (USD$<100 (kW h)−1) and superior performances, significant developments of redox and hybrid flow batteries have been made using various organic and inorganic redox couples in aqueous and nonaqueous electrolytes. To further improve the energy and power densities, desirable properties of these electrolytes are essential. In this article, comparisons and latest advances of these electrolytes in terms of stabilities, redox potentials, solubilities, viscosities, conductivities, opportunities, and economic prospects are discussed.